Strategies employed for information transfer and relation building in intercultural communication – A cross-cultural study - Kiliańska-Przybyło, Grażyna (East European Journal of Psycholinguistics, 2023)
The aim of the study is to examine strategies used in intercultural encounters by Polish and Turkish students of Foreign Languages (n1=50, n2=50, respectively) who have experienced intercultural communication. Intercultural encounters are viewed as ‘language-in-action’ situations because they provide a rich source of information about linguistic devices used during intercultural exchanges, sources of misunderstanding and miscommunication, and strategies implemented to transfer information or maintain conversational involvement of the interlocutors. This study offers some insights into the frequency and variety of the strategies used in intercultural encounters. It was conducted as a small-scale project, with the Critical Incident Technique and questionnaires administered to collect data. The research participants (C1/C2 levels of proficiency) were supposed to produce written narratives describing the most memorable intercultural encounters and report on intercultural communication strategies. Their narratives were later analysed to identify strategies applied to manage intercultural communication and achieve communicative goals (e.g. maintaining contact and/or conveying necessary information). Research findings show that Proactively seeking clarification and Building intercultural connection or relationship were the most frequent strategies used by these two groups. However, research results also suggest that the choice of strategies depends on such factors as the participants’ level of language proficiency, their cultural background or the quality and quantity of intercultural contacts. Cross-cultural analysis indicates that Turkish students are more socially- and culturally oriented, whereas Polish students display a tendency to focus more on cognitive and linguistic aspects of intercultural encounters. Findings from the study can be of help for educators and trainers involved in researching intercultural communication, strategic involvement and training.Author: Grażyna Kiliańska-Przybyło,    0000-0002-0185-5911 grazyna.kilianska-przybylo@us.edu.pl